2004
DOI: 10.1097/01.prs.0000133173.71201.3c
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Pain Pump Catheter in Immediate Autologous Breast Reconstruction

Abstract: The purpose of the investigation was to evaluate the efficacy of a slow bupivacaine infusion at postoperative surgical sites in immediate breast reconstruction patients. This prospective study included 16 patients who underwent autologous breast reconstruction with a latissimus dorsi pedicled flap immediately after mastectomy. A two-site infusion kit with dual split-flow catheters was secured at the operative sites before skin closure. A spring-loaded disposable pump then infused 0.25% bupivacaine at a rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 7 publications
2
25
0
Order By: Relevance
“…In addition, patients who require radiation therapy will avoid the potential radiation-induced problems that are known to occur with immediate reconstructions [23••]. • Continuous infusion pain pumps used postoperatively for up to 72 hours have been shown to dramatically affect pain ratings, along with significantly decreasing oral and intravenous narcotic usage in patients after autologous reconstructions [57] and tissue/expander reconstructions [58••]. The pump is portable, disposable, and pressure driven to deliver 0.25% bupivacaine through small catheters into the operative sites.…”
Section: Nipple and Areolar Reconstructionmentioning
confidence: 99%
“…In addition, patients who require radiation therapy will avoid the potential radiation-induced problems that are known to occur with immediate reconstructions [23••]. • Continuous infusion pain pumps used postoperatively for up to 72 hours have been shown to dramatically affect pain ratings, along with significantly decreasing oral and intravenous narcotic usage in patients after autologous reconstructions [57] and tissue/expander reconstructions [58••]. The pump is portable, disposable, and pressure driven to deliver 0.25% bupivacaine through small catheters into the operative sites.…”
Section: Nipple and Areolar Reconstructionmentioning
confidence: 99%
“…Regarding infusion pumps at the surgical site, Baroody et al [6] assessed their costs and efficacy in breast reconstruction, estimating that the added costs of the catheter and additional medication were US$280 per 48 h, while the costs of intravenous analgesic drugs were US$65 to 150; nevertheless, its use, given the efficacy of the technique, was recommended.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the delivery of drugs by continuous infusion through catheters [3,4] has been used in both simple and modified mastectomies [5,6], as well as in a wide range of other types of surgeries [7][8][9][10][11][12][13], and recently in modified radical mastectomy [14] in a double-blind, placebo-controlled, parallel-group randomized clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that patients were more comfortable and used less narcotics. Baroody et al (5), in a study of 16 prospective, immediate, autologous latissimus dorsi breast reconstruction with historical controls, showed that continuous infusion of bupivacaine decreased pain and narcotic use significantly in the postoperative period. They also observed that there was a reduction in PONV.…”
Section: Pain Pumps In Breast Surgerymentioning
confidence: 99%
“…Pain pumps using continuous infusions of local anesthetic agents have been studied in various types of surgical procedures (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). They are placed in the surgical site and local anesthetics are delivered to the site.…”
Section: Pain Pump Kitsmentioning
confidence: 99%